Pengaruh Profitabilitas, Likuiditas, Dan Leverage Terhadap Keputusan Hedging: Studi Empiris pada Perusahaan Sektor Barang Konsumen Non Primer yang Terdaftar di Bursa Efek Indonesia Periode 2018 – 2021 - Safitri, Raden Hana; Nuraini, Airin; Setiawan, Hendra (Program Vokasi dan LPPM IBI Kesatuan, 2023)
International trade is mostly carried out by companies in Indonesia. International trade obviously related with foreign currency exchange rates. This exchange rate is fluctuating that can cause company has a financial risk such as declining company profit, increasing corporate debt, and weakening financial performance. To conques this problem, hedging decisions are one way to maintain exchange rates and minimize financial risks that may occur. Therefore, this study aims to determine the effect of profitability, liquidity, and leverage on hedging decision. This study used secondary data with a quantitative approach, where the sample selected in this study used purposive sampling techniques. The population of non primary consumer goods sector company listed on the IDX is 136 companies to 16 companies selected by criteria, so there are 64 samples. The data analysis method that used in this study is logistic regression analysis. Research data is processed using SPSS software. The result of this study showed that profitability had a positive regression coefficient with a significance value of 0,001 < 0,05, indicating that profitability had a positive and significant effect on hedging decision. Liquidity had a significance value of 0,003 < 0,05, indicating that liquidity had a negative effect and significant effect on hedging decision. Leverage had a significance value of 0,642 > 0,05, indicating that leverage had no effect on hedging decision. Profitability, liquidity, and leverage simultancously had a significance value of 0,000 < 0,05, indicating that profitability, liquidity, and leverage simultancously had a significant effect on hedging decision in non primary consumer goods sector company listed on the Indonesia Stock Exchange for the period 2018-2021. Keywords: Profitability, Liquidity, Leverage, Hedging Decision